A Pilot Study of the Development of the Health Behavior Model for the Prevention of Hand, Foot and Mouth Disease among Children and Caregivers in Child Development Center, Sadao District, Songkhla Province - Amporn, Sarawut; Sukhonthachit, Penmat; Ditsuwan, Thanittha (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2018)
This action research aimed to conduct a pilot study and to examine the efficiency of the health behavior model among children and caregivers for the prevention of hand, foot and mouth disease in the child development center in Sadao district, Songkhla province. This study included 65 children and 15 caregivers and conducted from July 2017 to October 2017. The instrument used was a health behavior observation forms for children and caregivers. Data were analyzed using descriptive statistics and one-way repeated measures ANOVA and presented as the percentage, mean and standard deviation by comparing the health behaviors of children and caregivers before and after one and three-month implementation of the health behavior model. When subjecting the health behaviors model in children and caregivers to examine the effectiveness, it was found that the mean score of the model statistically significant increased after one and three months of the study with significance level of α=0.05. However, the knowledge and the involvement of parents and caregivers for disease prevention, including the environment of the center should be further explored. These factors, taken together, could help to reduce the spread of hand, foot and mouth disease in the area and be a proactive approach for the prevention and control of this disease in other child development centers.